Practical instruction and mathematics academic achievement in selected Ugandan secondary schools - Murangira, Frank; Uworwabayeho, Alphonse; Twagilimana, Innocent (Institute of Advanced Engineering and Science, 2025)
The challenges met in academic achievement of learners in mathematics at secondary school level are enormous. Taking a glance at the academic achievement of learners in mathematics in Uganda, poor academic achievement becomes more and more striking. It is a puzzle to understand the origin of the causes of this poor academic achievement despite the prominence and significance bestowed upon it by the Ugandan government and society at large. It is accepted that ways mathematics is taught have high impact on learners’ achievements. Therefore, an investigation on the effect of practical instruction (PI) on learners’ academic achievement in mathematics is timely. The study was carried out using a total of 383 senior three students from eight secondary schools both private and government aided schools. It involved a quantitative approach using mathematics achievement test (MAT). The results revealed that PI affects learners’ academic achievement positively in mathematics. They showed that learners that were taught using PI improved in their academic achievement more than their counterparts in the post-test examination. Considering these findings, the study recommends proactive measures to ensure the widespread adoption of PI strategies in secondary school classrooms. This includes revising curriculum standards, providing teacher training programmers, and allocating resources to support the implementation of PI, thereby fostering learning outcomes in mathematics.